UiTM News Hub: Academy of Language Studies, UiTM Perlis successfully organised workshop on writing innovation abstracts for beginners / Dr Razlina Razali and Anis Maesin - Razali, Razlina Dr; Maesin, Anis (2022)
ARAU, April 8, 2022 - The Academy of Language Studies, UiTM Perlis, has successfully organised its first University Social Responsibility (USR) Programme for 2022 by holding the Writing Innovation Abstracts for Beginners Workshop on Friday.